Hollow Bimetallic Zinc Cobalt Phosphosulfides for Efficient Overall Water Splitting. Issue 2 (11th December 2018) - Liang, Zuozhong; Yang, Zhiyuan; Dang, Jingshuang; Qi, Jing; Yuan, Haitao; Gao, Jinpeng; Zhang, Wei; Zheng, Haoquan; Cao, Rui
Abstract: Bimetallic sulfides with earth‐abundant transition‐metal elements are proposed to enhance the electrocatalytic activities. Further replacement of S atom by less electronegative P atom improves the electrocatalytic performance of OER and HER. Herein, hollow bimetallic zinc cobalt phosphosulfides (Zn0.3 Co2.7 S3 P) are synthesized by a two‐step process. The optimal catalyst of Zn0.3 Co2.7 S3 P with particle size of 50 nm displays an excellent electroactivity and long‐term durability toward efficient overall water splitting process in alkaline medium. The excellent bifunctional electrocatalytic performance may be ascribed to the synergistic effect of hollow structure, anion substitution tuning and unique size control. Abstract : One catalyst, two reactions : Hollow bimetallic zinc cobalt phosphosulfides were synthesized by a two‐step process and used as electrocatalysts for overall water splitting. The optimal catalyst of Zn0.3 Co2.7 S3 P with particle size of 50 nm displays an excellent electroactivity and long‐term durability toward efficient overall water splitting in alkaline medium.